Mortality Over Long-term Follow-up for People With HIV Receiving Longitudinal Care and Antiretroviral Therapy in Rural Haiti. (11th August 2020) - Richterman, Aaron; Leandre, Fernet; Jerome, J Gregory; Tsai, Alexander C; Ivers, Louise C
Abstract: Background: Deaths from HIV have fallen dramatically with the increasing availability of fully suppressive antiretroviral therapy (ART), and yet HIV remains the ninth leading cause of death in low-income countries. As more people with HIV enter care and receive ART, the focus will need to shift from expanding ART to including long-term program effectiveness and outcomes for people with HIV already engaged in care. Methods: We evaluated risk factors for mortality among people with HIV on ART receiving longitudinal care in rural Haiti. We assessed baseline characteristics using a household survey and abstracted clinical characteristics from the electronic record. We used multivariable Cox regression models to identify risk factors for mortality. Results: There were 464 people included in this study with a median follow-up (interquartile range [IQR]) of 69 (44–77) months, during which time 37 (8%) were lost to follow-up and 118 (25%) died (median time to death [IQR], 29 [12–53] months). After adjustment, poverty (adjusted hazard ratio [AHR], 1.12 per 10–percentage point increased probability; 95% CI, 1.01–1.24) and single marital status (AHR, 1.59; 95% CI, 1.08–2.36) were associated with increased mortality. Age (AHR, 0.78 per 10-year increase; 95% CI, 0.64–0.94), role function quality of life (AHR, 0.75 per quintile increase; 95% CI, 0.62–0.90), and CD4 count (AHR, 0.66 per 100 cells/μL; 95% CI, 0.58–0.75) were associated with decreased mortality. Conclusions: Poverty, marital status, and quality of life were associated with mortality. Social protection should be evaluated as a strategy to reduce mortality for people with HIV in concert with increasing access to ART.